2006
DOI: 10.1111/j.1462-5822.2006.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles for excretory-secretory cysteine proteases during tissue invasion of Paragonimus westermani newly excysted metacercariae

Abstract: SummaryParagonimus westermani is a trematode parasite, which causes pulmonary and/or extrapulmonary granulomatous disease in humans. Successful invasion of the host tissue is critical for the survival of this tissue-invasive parasite. The enzymatic hydrolysis of host proteins is clearly a prerequisite of this process. In this study, we have investigated the functional roles of the excretory-secretory cysteine proteases of P. westermani newly excysted metacercariae (PwNEM) in tissue invasion. The 27 and 28 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…On the basis of the substrate specificity, the 27 kDa CP purified from the ESP shared similarity with sparganum cathepsin S [13] or Fasciola hepatica cathepsin L [14], whereas the 28 kDa CP had mammalian cathepsin B-like properties [15]. A recent report has shown that the proteolytic activity of the 27 kDa CP against a Z-FR-AMC substrate was higher than that of the 28 kDa CP, and that the 28 kDa, but not the 27 kDa, CP directly facilitated tissue penetration by the PwNEM [2]. These collective data strongly suggest that these 2 cysteine proteses secreted by PwNEM have a different role in the host immune functions during tissue invasion in vivo.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…On the basis of the substrate specificity, the 27 kDa CP purified from the ESP shared similarity with sparganum cathepsin S [13] or Fasciola hepatica cathepsin L [14], whereas the 28 kDa CP had mammalian cathepsin B-like properties [15]. A recent report has shown that the proteolytic activity of the 27 kDa CP against a Z-FR-AMC substrate was higher than that of the 28 kDa CP, and that the 28 kDa, but not the 27 kDa, CP directly facilitated tissue penetration by the PwNEM [2]. These collective data strongly suggest that these 2 cysteine proteses secreted by PwNEM have a different role in the host immune functions during tissue invasion in vivo.…”
mentioning
confidence: 94%
“…P. westermani newly excysted larvae (PwNEM) secrete excretory-secretory products (ESP) that are mainly composed of 2 cysteine proteases of 27 and 28 kDa size, which are required for excystment of the metacercariae [1], successful larval tissue invasion [2], and evasion of the host's immune system [3]. Moreover, recent studies have shown that proteases in the ESP secreted by PwNEM regulate IL-8 production and the life span of human eosinophils [4,5].…”
mentioning
confidence: 99%
“…In this case, although the exact cause is unknown, Paragonimus spp remained only in the abdominal cavity and right adrenal gland. There was no obvi- Recent studies suggest that enzymatic hydrolysis of host proteins by cysteine proteases is an essential step in host cell invasion and migration [17,18]. One hypothesis could be that there was some problem in this process which showed developmental stage-specific expression of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The entire assay was carried out employing a Z-LR-AMC substrate. Kang et al, 2004;Lustigman et al, 2004;Dvorak et al, 2005;Na et al, 2006). However, only limited biochemical and immunological studies on the cysteine proteases of cestode parasites have been done.…”
Section: Discussionmentioning
confidence: 99%